Pengaruh Capital Adequacy Ratio (CAR), Loan To Deposit Ratio (LDR) dan Non Performing Loan (NPL) Terhadap Return On Asset (ROA) pada PT. Bank Mandiri (Persero) Tbk - Wahyu Subono; Rizki Putri Adlina (Universitas Mohammad Husni Thamrin, 2020)
This research discusses how Capital Adequacy Ratio, Loan to Deposit Ratio and Non Performing Loan To Return On Asset At PT. Bank Mandiri (Persero) Tbk. This research is quantitative research in looking at the relation of variable to the object being studied more cause and effect. The Population and sample of this research is PT. Bank Mandiri (Persero) Tbk using secondary data of quarterly financial report period of 2007 until 2016. The research data was processed using SPSS 21 with classical assumption test, descriptive statistic and hypothesis test. The results of this research suggest to maintain the bank's function properly and carefully in distributing credit to reduce the high value of NPLs (non-performing loans). Capital reserves need to be considered because the condition of a bank too solvable will make it difficult for the bank itself to gain profit, by reducing the CAR value along to increasing the amount of fund disbursement. Utilize maximally liquidity owned banks to increase LDR by optimum credit channeling. Keywords: Capital Adequacy Ratio, Loan To Deposit Ratio, Non Performing Loan, Return On Asset